Development of a Microscale Red Blood Cell-Shaped Pectin-Oligochitosan Hydrogel System Using an Electrospray-Vibration Method: Preparation and Characterization. Issue 4 (October 2015) - Crouse, James Z.; Mahuta, Kirsten M.; Mikulski, Brandon A.; Harvestine, Jenna N.; Guo, Xiaoru; Lee, Jung C.; Kaltchev, Matey G.; Midelfort, Katarina S.; Tritt, Charles S.; Chen, Junhong; Zhang, Wujie
Purpose: To develop and characterize a microscale pectin-oligochitosan hydrogel microcapsule system that could be applied in such biological fields as drug delivery, cell immobilization/encapsulation, and tissue engineering. Methods: Microscale pectin-oligochitosan hydrogel microcapsules were prepared by using the vibration/electrostatic spray method. The morphology and chemistry of the hydrogel microcapsules were characterized by using scanning electron microscope (SEM) and Fourier Transform Infrared Spectroscopy (FTIR), respectively. The designed hydrogel microcapsule system was then used to study the responsiveness of the microcapsules to different simulated human body fluids as well as cell encapsulation. Results: The designed hydrogel microcapsule system exhibited a large surface area-to-volume ratio (red blood cell-shaped) and great pH/enzymatic responsiveness. In addition, this system showed the potential for controlled drug delivery and three-dimensional cell culture. Conclusion: This system showed a significant potential not only for bioactive-agent delivery, especially to the lower gastrointestinal (GI) tract, but also as a three-dimensional niche for cell culture. In particular, the hydrogel microcapsule system could be used to create artificial red-blood-cells as well as blood substitutes.